Effects of Failure Acceptance, Entrepreneurial Orientation, and Social Safety Net on Entrepreneurial Intention: A Moderated Mediation Analysis of Korean Employees - Yu Jin Chang; Arpine Martirosyan; Hae Wen Lim; Jae Wook Yoo (Behavioral Sciences)
This study aims to examine innovation using an entrepreneurial event model by exploring the effects of failure acceptance, entrepreneurial orientation, and social safety nets on entrepreneurial intention. A survey was conducted with employees in South Korea to collect data, which were analyzed statistically using SPSS version 27.0 and Macro 4.1. The findings indicate that the failure acceptance of South Korean employees does not directly influence their entrepreneurial intention; rather, it has a complete mediation effect through entrepreneurial orientation. This reflects the unique entrepreneurial culture in South Korea, where entrepreneurship is highly emphasized. Additionally, perceptions of social safety nets positively moderate the relationship between entrepreneurial orientation and entrepreneurial intention. The research highlights the significance and direction of studies in the entrepreneurial sector by considering national cultural differences and emphasizing the interaction between individual psychological traits and environmental factors. Furthermore, it presents South Korea’s distinctive entrepreneurial culture and offers elements that could enhance the entrepreneurial environment, thereby creating practical value.